PENDIDIKAN MULTIKULTURAL DI ASIA SELATAN; STUDI KOMPARATIF INDIA, BANGLADESH DAN PAKISTAN - Herawati Herawati; Brenny Novriansyah (Jurnal Pendidikan "EDUKASIA MULTIKULTURA", 2020)
The study purposed to describe the multicultural education in south Asia region i.e. India, Bangladesh, Pakistan, and to compare similarities and differences between those countries. The study designed as expost facto research, which used document study, interview, and observation as data collection method. The data analyzed through descriptive qualitative approach. The study showed that religious learning in Pakistan and Bangladesh as major Muslim population country seldomly not accommodate minor students or non-muslim students. The discrepancy of girl participants emerged lowest. It investigated that some materials are not accommodate multicultural education but tend to down grade local culture. In the contrary, India, the conflict often comes either between majority and minority or upper caste and lower caste. Both lower caste and unscheduled caste could not get feasible education services. There some materials described local culture with which contradicted to universal values.